The Role of Future Orientation as a Mediator Between Responsive Parenting and Adolescent Identity Formation - Tyvania Shalsabilla Wilhelmina Patty; Darmawan Muttaqin (Universitas Ahmad Dahlan, 2023)
Responsive parenting contributes to positive adolescent development, including identity formation. However, previous research has not described the relationship between responsive parenting and identity formation. This research examines the role of future orientation as a mediator in the relationship between responsive parenting and identity formation. A total of 450 adolescents were involved in the study, which included early (12-15 years old), middle (15-18 years old), and late (18-20 years old) adolescents. Additionally, the Parental Responsiveness Scale, the Future subscale from the Zimbardo Time Perspective Inventory, and the Utrecht-Management of Identity Commitment Scale were used to assess responsive parenting, future orientation, and identity formation. According to the results, future orientation can mediate the relationship between responsive parenting with commitment and in-depth exploration. Furthermore, this research found that responsive parenting can predict reconsideration of commitment. These findings indicate that this parenting has two sides, one being it can lead adolescents to develop future orientations, resulting in optimal identity formation. On the other hand, it directs adolescents to reconsider their commitments as an indicator of a suboptimal identity formation process.